Certain Aspects of the Constitutional Review of Legal Omissions - Masnevaitė, Elena; Miliuvienė, Jolita (Vilnius University Open Series, 2024)
The absence of the appropriate legislation in some areas of social relations or, in other words, the situation when certain social relations are not legally regulated, although there is a need to regulate them, implies the existence of a legal gap (lacuna legis). A legislative omission is a special legal gap because it is prohibited by Law, first of all, by supreme law – the Constitution. The constitutional competence to investigate the constitutionality of legal gaps prohibited by Law was disclosed by the Constitutional Court of the Republic of Lithuania at the beginning of the second decade of its activity. The competence to declare the existence of legislative omissions was derived from the power of the Constitutional Court, stipulated in the Constitution, to administrate constitutional justice and to guarantee the supremacy of the Constitution, with a view to the better protection of the human rights and freedoms. It was argued that not only a particular legal regulation, but also the absence of it, when the necessity to establish such a legal regulation stems from the Constitution, can lead to the violation of the human rights and freedoms. The article analyses the conception of the legislative omission in the jurisprudence of the Lithuanian Constitutional Court and the constitutional review institutions of some other states. It also discusses the reasons which determined the choice of the model of the constitutional review of legislative omissions in Lithuania. Finally, the article examines some cases of the review of the constitutionality of legal gaps in the jurisprudence of the Lithuanian Constitutional Court. The authors argue that the legislature has the duty under the Constitution to adopt a legal regulation not only in those cases where the Constitutional Court finds a legal omission and recognizes that the challenged legal act is non-compliant with the Constitution, but also in those cases where, in the official constitutional doctrine, the Constitutional Court formulates some constitutional requirements which presuppose the establishment of a missing legal regulation.
Keywords: legal gap; legislative omission; Constitutional Court; constitutional review of legislative omissions; duty to enact a legal regulation